Sistem Informasi Manajemen Buku Kas Elektronik untuk Pembayaran SPP - M Syahid Nur Wahid; Alfi Nur Afida Arista; Firmansyah Firmansyah; Nirwana Nirwana; Zulfahmi Zulfahmi (PT. Lontara Digitech Indonesia, 2023)
This research aims to develop an efficient and effective web-based Student Development Contribution (SPP) payment information system and test its performance in enhancing the speed, accuracy, and precision of SPP payment report generation. The Agile methodology is employed for system development, emphasizing flexibility and adaptability to address potential future requirements. The findings indicate successful development of the web-based SPP payment information system. The conducted tests confirm its ability to deliver optimal performance, safeguard sensitive data effectively, and function in accordance with specified requirements. The system enhances administrative efficiency in SPP payment processes at educational institutions by ensuring accurate data management, swift payment processing, and responsiveness to changing needs.